A new approach for pancreatic tissue engineering: human endometrial stem cells encapsulated in fibrin gel can differentiate to pancreatic islet beta‐cell. (3rd July 2014) - Niknamasl, Azadeh; Ostad, Seyed Nasser; Soleimani, Mansoureh; Azami, Mahmoud; Salmani, Maryam Kabir; Lotfibakhshaiesh, Nasrin; Ebrahimi‐Barough, Somayeh; Karimi, Roya; Roozafzoon, Reza; Ai, Jafar
Abstract Metabolic diabetes mellitus as the most serious and prevalent metabolic disease in the world has various complications. The most effective treatment of type I diabetes seems to be islet cell transplantation. Shortage of donors and difficult procedures and high rate of rejection have always restricted this approach. Tissue engineering is a novel effective solution to many medical problems such as diabetes. Endometrial mesenchymal stem cells as a lineage which have the potential to differentiate to mesodermal and endodermal tissues seem to be suitable for this purpose. Fibrin hydrogel with a high degree of biocompatibility and specific properties making it similar to normal pancreas seems to be an ideal scaffold. After successfully isolating stem cells (hEnSCs) from human endometrium, a three‐step protocol was used to differentiate them into pancreatic beta cells. Fibrin was used as 3D scaffold. After 2 weeks, cells formed clusters like islets cells, and secretion of insulin was measured by chemiluminescence. PDX1, proinsulin, and c‐peptide as special markers of β cells were detected by immunofluorescence. Expression of glucagon, PDX1, and insulin genes in mRNA level was detected by Real time PCR and gel electrophoresis. The former showed higher levels of gene expression in 3D cultures. SEM analysis showed good integrity between cells and scaffold. No toxicity was detected with fibrin scaffold by MTT assay.